DETERMINATION OF THE PHYTOCHEMICALS, ANTIOXIDANTS AND ANTIMICROBIAL PROPERTIES OF A RARE AND ENDEMIC PLANT XANTHOPHYLLUM ARNOTTIANUM WIGHT OF WESTERN GHATS, INDIA - PICHAN M. SALIM; JOSEPH JOHN (The Journal of Research ANGRAU, 2025)
Xanthophyllum arnottianum Wight is a rare and endemic plant and is having limited distribution  in biodiversity hot spot of Western Ghats of India. The study was conducted in the year 2023 to  document the phytochemical constitution, antioxidant potential and antimicrobial properties of  the leaves of this plant. Study revealed that Xanthophyllum arnottianum Wight is a rich source of many of the phytochemicals of which flavonoids composition was found to be 0.08mg/ml-1, tannins  0.57mg/ml-1. Total antioxidant capacity was found to be 0.33mg/ml-1 and enzymatic antioxidants  (peroxidase-0.12mg/ml-1). GCMS analysis identified ten principal in the leaf extracts of X.  arnottianum. This species of plant is recognized for its significant phytochemical profile of  importance such as 3,5-Dimethoxyacetophenone, Neophytadiene, Phytol and Acetate. Antimicrobial properties of the methanolic extract of the plant indicated that this plant possesses antibacterial activity against all the three tested microorganisms (Klebsiella pneumoniae (8mm), Staphylococcus aureus (20mm) and Escherichia coli (7mm). This research serves as an initial endeavour that shed light into the wealth of novel biomolecules that are remained as hidden in the plant kingdom.